Companion-Cell Specific Localization of Sucrose Synthase in Zones of Phloem Loading and Unloading. - Nolte, K. D. (1993)
An immunohistochemical approach was used in maize (Zea mays) and citrus (Citrus paradisi) to address the previously noted association between sucrose synthase and vascular bundles and to determine the localization of the low but detectable levels of sucrose synthase that remain in leaves after the import-export transition. Sucrose synthase protein was immunolocalized at the light microscope level using paraffin sections reacted with rabbit sucrose synthase polyclonal antisera and gold-conjugated goat anti-rabbit immunoglobulin G. Immunolabel was specifically observed in phloem companion cells of minor and intermediate veins in mature leaves of both species. Similar localization was apparent in the midrib of mature citrus leaves, with additional labeling in selected files of phloem parenchyma cells. A clear companion-cell specificity was evident in the phloem unloading zone of citrus fruit, where high activity of sucrose synthase has been demonstrated in vascular bundles during periods of rapid import. Sucrose synthase protein was not associated with adjacent cells surrounding the vascular strands in this tissue. The companion-cell specificity of sucrose synthase in phloem of both importing and exporting structures of these diverse species implies that this may be a widespread association and underscores its potential importance to the physiology of vascular bundles.